2015
DOI: 10.20472/es.2015.4.4.002
|View full text |Cite
|
Sign up to set email alerts
|

Macroeconomics Determinants of External Debt in Malaysia

Abstract: Abstract:The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 18 publications
(6 reference statements)
2
4
0
Order By: Relevance
“…Applying the vector error correction model to a dataset spanning the period 1970-2013, Udoh and Rafik (2017) showed that capital expenditure increases external debt, whereas economic growth reduces it for the case of Malaysia. Lau, Lee, and Apir (2015) also reported a similar finding for Malaysia. Employing the autoregressive distributed lag model and using data on Turkey, Özata (2017) revealed that budget deficit and exchange rate escalate external debt, whereas savings reduce it.…”
Section: Empirical Reviewsupporting
confidence: 67%
See 1 more Smart Citation
“…Applying the vector error correction model to a dataset spanning the period 1970-2013, Udoh and Rafik (2017) showed that capital expenditure increases external debt, whereas economic growth reduces it for the case of Malaysia. Lau, Lee, and Apir (2015) also reported a similar finding for Malaysia. Employing the autoregressive distributed lag model and using data on Turkey, Özata (2017) revealed that budget deficit and exchange rate escalate external debt, whereas savings reduce it.…”
Section: Empirical Reviewsupporting
confidence: 67%
“…Common determinants of external debt reported in existing literature are economic growth, imports, population, foreign exchange reserves, total debt service, poverty, income instability, depreciation of the currency, budget deficit, exchange rate, trade openness, terms of trade, inflation, interest rate, national savings, and financial development (Abdullahi, Bakar, and Hassan 2015;Bittencourt 2015;Lau, Lee, and Apir 2015;Vighneswara 2015;Lau and Lee 2016;Al-Fawwaz 2016;Belguith and Omrane 2017;Özata 2017;Udoh and Rafik 2017;Chiminya, Dunne, and Nikolaidou 2018;Chirwa and Odhiambo 2018;Adamu 2019;Brafu-Insaidoo et al 2019;Fatukasi et al 2020). For instance, Vighneswara (2015) and Beyene and Kotosz (2020a) asserted that government expenditure is one of the key factors that increase external debt due to budget deficits, which compel governments to borrow.…”
Section: Introductionmentioning
confidence: 99%
“…(2014),Kolasa & Wesołowski (2020),Matikainen et al (2017), andMeegan et al (2018).This research is in concordance with previous studies byQureshi & Liaqat (2020),Kumar et al (2019),Dailami & Leipziger (1998),Wijayanti & Rachmanira (2020),Lau & Lee (2016),Jones (2014), andMudzingiri (2014), which investigated the dynamics of foreign debt about infrastructure and epidemic budget allocations, net exports, and the consumer price index. In developing countries, infrastructure budgets are still largely financed through foreign debt.…”
supporting
confidence: 90%
“…Imimole et al (2014) found that the main determinants of Nigeria's external debt are debt service, gross domestic product, and exchange rate. Lau et al (2015) found short run causality relationship between the macroeconomic indicators and the external debt and in Malaysia covering the period between 1970 and 2013. Abdullahi et al (2015) examined the macroeconomic factors of external debt accumulation in Nigeria for the 1980 to 2013 period.…”
Section: Theoretical Framework and Literature Reviewmentioning
confidence: 91%